Interventions to support the re-establishment of breastfeeding and their application in humanitarian settings: A systematic review - Amat Camacho, Nieves; Von Schreeb, Johan; Della Corte, Francesco; Kolokotroni, Ourania (My University, 2023)
In 1998, the World Health Organisation (WHO) published general guidelines proposing essential measures to achieve relactation. Yet, increased knowledge about the practical set-up of relactation support interventions in different contexts is needed, especially in humanitarian settings, where nonbreastfed infants are particularly at risk. This study aimed to compile and assess the characteristics, outcomes and factors influencing the implementation of relactation support interventions reported since the latest WHO recommendations. We conducted a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, undertaking a search from Medline, Embase, PubMed Central, Web of Science, Global Health and CINAHL electronic databases. Studies published in English and Spanish, reporting characteristics and outcomes of relactation support provided to non-(breastfeeding) BF mothers with infants aged less than 6 months were included. Data were analysed by narrative synthesis and the Johanna Briggs Institute Critical Appraisal Tools were used for quality assessment. Overall, 16 studies met the inclusion criteria. Most were observational and conducted in middle-income countries, only one focused on humanitarian settings. Studies reported inpatient and community-based interventions, which generally followed WHO recommendations for relactation. In 13 out of 16 studies, over 80% of mothers restarted BF after receiving relactation support. Enabling factors included younger infant age, shorter lactation gap, mother's strong motivation, family support, and continuous skilled support. Although current literature suggests that intensive relactation support can contribute to re-establish BF, its application and effectiveness in humanitarian settings remain uncertain. Further research is needed to explore the effectiveness, feasibility and acceptability of different approaches to relactation support, especially in humanitarian settings.
Keywords: artificial feeding; breast feeding; disasters; humanitarian; infant nutrition; re-lactation